1999
DOI: 10.1021/bi990983g
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Axial Ligand in Type 1 Cu Centers Studied by Point Mutations of Met148 in Rusticyanin

Abstract: Type 1 Cu centers in cupredoxins, nitrite reductases, and multi-copper oxidases utilize the same trigonal core ligation to His-Cys-His, with a weak axial ligand generally provided by a Met sulfur. In azurin, an additional axial ligand, a carbonyl oxygen from a Gly, is present. The importance of these axial ligands and in particular the Met has been debated extensively in terms of their role in fine-tuning the redox potential, spectroscopic properties, and rack-induced or entatic state properties of the copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
102
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 27 publications
12
102
0
3
Order By: Relevance
“…Finally, the Met121Leu mutation also shifted the reduction potential ∼60-80 mV higher in each mutant (Table 2), which is consistent with reports by others and reasonable considering a stabilization of Cu(I) by the resulting trigonal ligand set [33,47,[85][86][87][88][89][90][91][92]. Overall, the Met121Leu triple Phe substituted mutant (Met121Leu + Leu33Phe/Met44Phe/ Leu86Phe azurin) showed the highest potential (503 mV vs. NHE), with a value over 140 mV higher than WT azurin.…”
Section: Redox Potential Measurementssupporting
confidence: 90%
“…Finally, the Met121Leu mutation also shifted the reduction potential ∼60-80 mV higher in each mutant (Table 2), which is consistent with reports by others and reasonable considering a stabilization of Cu(I) by the resulting trigonal ligand set [33,47,[85][86][87][88][89][90][91][92]. Overall, the Met121Leu triple Phe substituted mutant (Met121Leu + Leu33Phe/Met44Phe/ Leu86Phe azurin) showed the highest potential (503 mV vs. NHE), with a value over 140 mV higher than WT azurin.…”
Section: Redox Potential Measurementssupporting
confidence: 90%
“…The 96 mV increase in redox potential in M144L is consistent with that observed in the equivalent M148L mutation in rusticyanin, where an increase of w130 mV was observed. 11 Indeed, the T1Cu sites of M144L AxNiR and M148L rusticyanin 12 are similar in structure. The T1Cu site is also similar to those seen in laccase 13 and ceruloplasmin, 14 which have leucine as the axial ligand and high redox potentials, although in the case of ceruloplasmin Leu adopted a different rotamer such that the nearest atom was w3.7 Å from the Cu.…”
Section: Nature Of the Axial Ligand And Redox Potentialmentioning
confidence: 96%
“…Site-directed point mutation of the axial ligand has been carried out for blue copper proteins. It has been reported that the replacement of Met at the axial ligand by Gln causes the negative shift in the formal potential of the type I Cu site in blue copper proteins [7][8][9][10][11]. In contrast, the replacement of Gln by Met causes the positive shift in the formal potential [12,13].…”
Section: Introductionmentioning
confidence: 99%